Prospective Outcome Analysis of Adolescents and Young Adults Receiving Treatment from a Tertiary Cancer Hospital in Bangladesh (TAJ: Journal of Teachers Association, 2022)
Background: Malignancies in adolescents and young adults (AYAs) are increasing day by day with increasing their death occurrences but a few clinical and epidemiological data from developing countries. There are 72006601.45(44.2%) people under this 15-39 years age group in Bangladesh. They are in vital age group not only for their own development but also for their country and for the world. This study was aimed to find out the outcome of treatment and causes of death.Methods: The study was an observational study. All histologically confirmed cancer patients aged 15-39 years who completed treatment under medical oncology department in National Institute of Cancer Research and Hospital (NICRH) from Jan.2016 to Dec.2017(24 months). Of them 593 patient were included for the study. Their follow up were taken over phone or departmental follow up registries up to May, 2019. Information was prospectively studied.Results: Total 593 patients were enrolled for this study. Of them, male(M) 295(49.75%), female(F)298(50.25%) and M: F=1:1.01. After follow up, it was documented that 170(28.67%) patients were untraceable whose 63(10.62%) patients had no contact number. Among the remaining patients 473, 170(35.94%) patients were died due to anorexia 162(95.3%), both nausea and vomiting 90(53%), pain and fever 65(38.24%), diarrhea 57(33.53%), respiratory distress 38(22.35%), cachexia 37(21.76%), bleeding and generalized swelling 18(10.60%), opportunistic infection 10(5.88%), stroke 3(1.176%), surgical complication 2(1.18%). Of the died patient’s male were 96, female was 74 and M: F death ratio was 1.3:1. The leading causes of death, according to specific disease, were lung cancer 11(61%), head neck cancer 12(57%), sarcoma 56(46%), GIT (gastrointestinal tract) cancer 39(40.63%) and leukemia 12(35%). Least death occurred in GCT (germ cell tumor) 1(4.34%) and lymphoma 7(9%). Alive patients were 240. Of them male were 84, female was 156 and the ratio was M:F=1:1.86. According to specific disease, the highest survival was in testicular malignancy 18(85.71%), breast cancer 88(71%), FGT (female genital tract) 26(70%), lymphoma 44(59%) and GIT malignancy 42(43.75%).Conclusion: In AYA the death occurrences were 170(35.94%) and tract out of follow up were 170(28.67%). This high death occurrence dangerously alarming for developing countries as youth are majority of total population in developing countries. So Methods should be searched to reduce the AYA death occurrences.TAJ 2021; 34: No-2: 108-113